Catalytic pyrolysis of bamboo in a bubbling fluidized-bed reactor with two different catalysts: HZSM-5 and red mud for upgrading bio-oil. (April 2020) - Ly, Hoang Vu; Park, Jeong Woo; Kim, Seung-Soo; Hwang, Hyun Tae; Kim, Jinsoo; Woo, Hee Chul
Abstract: Bamboo has been considered a potential feedstock of energy for the future. It can be subjected to the pyrolysis for biofuels production. The thermogravimetric analysis (TGA) combined with differential thermogravimetric analysis (DTG) for bamboo was carried out prior to pyrolysis. The thermal degradation of bamboo was mainly between 230 and 420 °C. The conventional pyrolysis of bamboo was investigated in a bubbling fluidized-bed reactor using silica sand. The product distribution and composition of pyrolysis bio-oil were dependent on biomass component and operating conditions such as pyrolysis temperature, fluidization velocity, and particle size of biomass. The fractional catalytic pyrolysis of bamboo was also studied to upgrade the pyrolysis vapor, using HZSM-5 and red mud. The highest yield of bio-oil was 54.03 wt% compared to 49.14 wt% and 50.34 wt% of HZSM-5 and red mud catalyst, respectively. In the red mud catalytic pyrolysis, the oxygen content was rejected from pyrolysis vapor mostly via decarboxylation to produce more CO2 than CO; in contrast, for the HZSM-5 catalytic pyrolysis, the production of CO through decarbonylation was more favored than CO2 . The main composition of catalytic pyrolysis bio-oil was 4-vinylphenol, which was employed as a raw material source to synthesize valuable material for energy storage. Highlights: HZSM-5 mainly removed oxygen from pyrolysis vapor through dehydration and decarbonylation. HZSM-5 promoted formation of methoxy phenolic and aromatic compounds. Red mud promoted demethoxylation and improved production of saturated phenol.